Vitamin D Deficiency New Insights - Fedotova, Julia (IntechOpen, 2023)
Vitamin D is a unique bioregulatory molecule that can be synthesized in the skin as well as obtained via dietary sources. Vitamin D and its specific role in numerous diseases is a hot topic of scientific research. This book presents new insights into the specific role of vitamin D deficiency in the pathophysiological and biochemical mechanisms of many diseases. It is organized into four sections that present the latest data from clinical and preclinical investigations of the consequences of vitamin D deficiency in children and in diseases such as COVID-19 as well as cardiovascular, metabolic, endocrine, and renal disorders.